Effect of Different Weather Parameters on Population of Stem Borer, Chilo partellus Swinhoe infesting Rabi Sorghum - Patel, D. R.; Purohit, M. S. (International Journal of Economic Plants, 2016)
Studies on population dynamics of Chilo partellus Swinhoe infesting sorghum was made during 2006-07 and 2007-08 in rabi season at Agricultural Research Station, N.A.U., Tanchha, dist. Bharuch. The incidence of pest begins from fourth week of November(0.06 larva plant -1) and continued up to first week of February with a peak activity in second and fourth week of December(0.15 larva plant -1). The abiotic factors, maximum, minimum and average temperature had significant negative association, while humidity, rainfall, rainy days and sunshine hours, wind velocity and evaporation had no significant association with C partellus on rabi sorghum.